EFEK EKSTRAK ETANOL AKAR CAKAR SETAN (Martynia annua L) TERHADAP AKTIVITAS SGPT DAN SGOT PADA TIKUS YANG DIINDUKSI CCl4 - Elisabeth Oriana Jawa La; Repining Tiyas Sawiji; Ni Ketut Esati (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2021)
SGPT and SGOT activity from ethanol extract of cakar setan root (Martynia annua L) was investigated. Phytochemical screening was carried out on ethanol extract of cakar setan root (Martynia annua L). The animals were grouped into five groups which consist of 5 rats for each group. The normal/healthy group was only given food and drink the negative control group was given an aqueous suspension of 1 % CMC , the positif control group was given tablets Curcuma at a dose of 200 mg/Kg BB, the group ethanol extract Martynia annua L were each given extract at a dose of 200 mg/Kg BB and 400 mg/Kg BB. All groups were treated for 21 days orally. On day 22 were given injection of CCl4 1.0 mL/kg intraperitoneally except healthy group. The rats blood was taken and analyzed through eye orbitalis sinus AST and ALT activities. The result were statistically analyzed using One Way ANOVA test followed by LSD test. Phytochemical screening ethanolic extract of Martynia annua L root positively contains flavonoids, alkaloids, tannin, phenolic, and terpenoids. The result study that ethanol extract of cakar setan root (Martynia annua L) has hepatoprotective effect of being able to reduce activities of SGPT and SGOT in CCl4 induce white rats.